2017
DOI: 10.1002/ana.25044
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of KIF14 cause primary microcephaly by impairing cytokinesis

Abstract: Our data corroborate the role of an impaired cytokinesis in the etiology of primary and syndromic microcephaly, as has been proposed by recent findings on CIT mutations. Ann Neurol 2017;82:562-577.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 35 publications
0
57
0
Order By: Relevance
“…The authors found that cerebral and cerebellar hypoplasia were a result of increased apoptosis and reduced proliferation during embryogenesis. Recently, KIF14 mutation was identified as the driver of a form of primary, autosomal recessive microcephaly in four families [53] . These independent families were from Pakistan, Saudi Arabia, and Germany, and encompassed a total of ten individuals with microcephaly and homozygous and compound heterozygous KIF14 mutations that resulted in aberrant splicing or truncated protein.…”
Section: Kif14 Is Mutated In Primary Microcephaly and Upregulated mentioning
confidence: 99%
“…The authors found that cerebral and cerebellar hypoplasia were a result of increased apoptosis and reduced proliferation during embryogenesis. Recently, KIF14 mutation was identified as the driver of a form of primary, autosomal recessive microcephaly in four families [53] . These independent families were from Pakistan, Saudi Arabia, and Germany, and encompassed a total of ten individuals with microcephaly and homozygous and compound heterozygous KIF14 mutations that resulted in aberrant splicing or truncated protein.…”
Section: Kif14 Is Mutated In Primary Microcephaly and Upregulated mentioning
confidence: 99%
“…The polarized form of cytokinesis in embryonic cortical NSCs is poorly understood, but may influence the segregation of organelles and apical fate determinants to daughter cells as they make fate choices. Recent findings that mutations in Kif20b and other midbody genes cause microcephaly in humans and mice suggest that brain development is especially sensitive to defects in cytokinesis (26,(35)(36)(37)(38)(39). To elucidate these issues, we developed methods to quantitatively analyze furrowing and abscission in NSCs of the developing cerebral cortex.…”
Section: Discussionmentioning
confidence: 99%
“…MCPH1 encodes 835 amino‐acid protein with reported roles at least in DDR, cell cycle control and maintenance of chromosomal integrity . Curiously, MCPH1 has also been identified as causative gene for primary microcephaly (OMIM #251200), a neurodevelopmental disorder defined by marked reduction in brain size, mental retardation and short stature . At cellular level, the key phenotype seen in these patients is premature chromosome condensation (PCC) .…”
Section: Introductionmentioning
confidence: 99%
“…5,7 Curiously, MCPH1 has also been identified as causative gene for primary microcephaly (OMIM #251200), a neurodevelopmental disorder defined by marked reduction in brain size, mental retardation and short stature. 8,9 At cellular level, the key phenotype seen in these patients is premature chromosome condensation (PCC). 10,11 During DDR, MCPH1 is also involved in the regulation of chromatin condensation status, as it is required to recruit and maintain ATP-dependent chromatin remodeling complex SWI/SNF at the sites of DNA lesion.…”
Section: Introductionmentioning
confidence: 99%